POTENSI PUPUK HAYATI UNTUK MENINGKATKAN HASIL PADI DI LAHAN RAWA - Muhimmatul Husna; Tiara Nofrianti; Septiana Anggraini; Wuri Prameswari; Umi Salamah (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2024)
[POTENTIAL OF BIOFERTILIZERS TO INCREASE RICE YIELD IN SWAMP LANDS] Nutrient unavailability is a major problem in swamp land due to flooded and acidic conditions. The use of biofertilizer, which can increase the availability of nutrients, is a solution to increase rice yields in swamp land. This research aimed to find out the improvement of the rice yield with an application of bacteria in biofertilizers in swampy land. One factor tested was the various doses of bacterial biofertilizer consisting of 1, 2, 3, and 4 g/50 g of paddy seeds, without bacteria as a control, arranged in a randomized block design with 3 replications. Rice seeds were soaked for 24 hours, then drained, and biofertilizer was applied as a seed treatment following the treatment doses. Seeding was carried out in trays measuring 15 cm high for 2 weeks. The inorganic fertilizer was applied at 75% of the recommended dose. The variables observed were plant height, number of tillers, number of productive tillers, percentage of empty grain, weight of 1000 seeds, and grain weight. The data observed were analyzed with an ANOVA at the 5% level and further tested with DMRT at the 5% level. The results showed that the bacteria in biological fertilizer can potentially increase the yield of swamp rice plants. A biofertilizer dosage of 4 g/50 g of seeds gave the highest yield in terms of grain weight per hill and per plot, as well as a weight of 1000 grains with an increase of yield of 14.32% compared to control.